2010
DOI: 10.1002/chem.200903315
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogels Composed of Organic Amphiphiles and α‐Cyclodextrin: Supramolecular Networks of Their Pseudorotaxanes in Aqueous Media

Abstract: Mixtures of N-alkyl pyridinium compounds [py-N-(CH(2))(n)OC(6)H(3)-3,5-(OMe)(2)](+)(X(-)) (1bCl: n = 10, X = Cl; 1cBr: n = 12, X = Br) and alpha-cyclodextrin (alpha-CD) form supramolecular hydrogels in aqueous media. The concentrations of the two components influences the sol-gel transition temperature, which ranges from 7 to 67 degrees C. Washing the hydrogel with acetone or evaporation of water left the xerogel, and (13)C CP/MAS NMR measurements, powder X-ray diffraction (XRD), and scanning electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 95 publications
0
15
0
2
Order By: Relevance
“…In der Zeit zwischen Annahme und Veröffentlichung dieses Manuskripts sind weitere beachtliche Beiträge zu diesem Thema erschienen, z. B. über photoresponsive Pseudopolyrotaxan‐Hydrogele auf der Grundlage konkurrierender Wirt–Gast‐Wechselwirkungen,64 Hydrogele aus organischen Amphiphilen und α‐Cyclodextrin65 oder die lichtinduzierte Proteinfreisetzung aus einem supramolekularen Hydrogel 66…”
Section: Addendumunclassified
“…In der Zeit zwischen Annahme und Veröffentlichung dieses Manuskripts sind weitere beachtliche Beiträge zu diesem Thema erschienen, z. B. über photoresponsive Pseudopolyrotaxan‐Hydrogele auf der Grundlage konkurrierender Wirt–Gast‐Wechselwirkungen,64 Hydrogele aus organischen Amphiphilen und α‐Cyclodextrin65 oder die lichtinduzierte Proteinfreisetzung aus einem supramolekularen Hydrogel 66…”
Section: Addendumunclassified
“…When the concentration is below the CPC, there is no significant change for the aggregation of 1. [16] In conclusion, based on easily available copillararene monomers, linear supramolecular polymers can be efficiently constructed driven by quadruple C À H···p interactions. This phenomenon indicated that temperature affects the aggregation of 1; when the temperature increases, the degree of polymerization decreases.…”
mentioning
confidence: 93%
“…In chloroform, the positive entropy term (DS) resulting from exclusion of the solvent from the cavity should also augment the binding by reducing the free energy of the system (DG) (Supporting Information, Scheme S1 caption). [16] In conclusion, based on easily available copillararene monomers, linear supramolecular polymers can be efficiently constructed driven by quadruple C À H···p interactions. Only two steps were required to prepare copillararene monomer 1 from commerically available compounds.…”
mentioning
confidence: 99%